Equations balanced on the previous day | Equations balanced on the next day |
[Co(NH3)6]Cl3 + 3 NaOH + 6 H2O = Co(OH)3 + 3 NaCl + 6 NH3*H2O
AgNO3(aq) + KCl(aq) = AgCl(aq) + KNO3(aq) =>
AgNO3(aq) + KCl(aq) = AgCl(aq) + KNO3(aq)
Te + I2 = TeI4 =>
Te + 2 I2 = TeI4
HNO3(aq) + NaHCO3(aq) = H2O + CO2(g) + NaNO3(aq) =>
HNO3(aq) + NaHCO3(aq) = H2O + CO2(g) + NaNO3(aq)
CH3CH2COOH + H2O = CH3COOH + H2 =>
2 CH3CH2COOH + 2 H2O = 3 CH3COOH + 2 H2
Al + NaOH + NaNO3 = Na2AlO2 + H2O + NH3 =>
4 Al + 7 NaOH + NaNO3 = 4 Na2AlO2 + 2 H2O + NH3
NaHCO3 + HCI = CO2 + H2O + NaCI =>
NaHCO3 + HCI = CO2 + H2O + NaCI
Li3PO4 + AgClO4 = Li3ClO4 + AgPO4 =>
Li3PO4 + AgClO4 = Li3ClO4 + AgPO4
Al(s) + Ag2S(s) + H2O(l) = Ag(s) + Al(OH)3(aq) + H2S(g) =>
2 Al(s) + 3 Ag2S(s) + 6 H2O(l) = 6 Ag(s) + 2 Al(OH)3(aq) + 3 H2S(g)
Pb(OH)2(aq) + OH{-}(aq) = Pb(OH)3{-}(aq) =>
Pb(OH)2(aq) + OH{-}(aq) = Pb(OH)3{-}(aq)
HCOOH + Cu2(OH)2CO3 = Cu(HCOO)2 + CO2 + H2O =>
4 HCOOH + Cu2(OH)2CO3 = 2 Cu(HCOO)2 + CO2 + 3 H2O
F2 + KCl = Cl2 + FK =>
F2 + 2 KCl = Cl2 + 2 FK
H2SiO3 = SiO2 + H2O =>
H2SiO3 = SiO2 + H2O
H2SO4 + K2Cr2O7 + CO = CO2 + Cr2(SO4)3 + K2SO4 + H2O =>
4 H2SO4 + K2Cr2O7 + 3 CO = 3 CO2 + Cr2(SO4)3 + K2SO4 + 4 H2O
Cd3(PO4)2(aq) + (NH4)2S(aq) = CdS + (NH4)3PO4 =>
Cd3(PO4)2(aq) + 3(NH4)2S(aq) = 3 CdS + 2(NH4)3PO4
CH3COOH + FeCl3 + H2O = Fe3(OH)2(CH3COO)6Cl + HCl =>
6 CH3COOH + 3 FeCl3 + 2 H2O = Fe3(OH)2(CH3COO)6Cl + 8 HCl
Fe3 + SCN = Fe(SCN)6 =>
Fe3 + 18 SCN = 3 Fe(SCN)6
SO3 + H2O = H2O(SO3) =>
SO3 + H2O = H2O(SO3)
MnO2 + MgCl2 + HNO3 = Mg(NO3)2 + Mn(NO3)2 + H2O + Cl2 =>
MnO2 + MgCl2 + 4 HNO3 = Mg(NO3)2 + Mn(NO3)2 + 2 H2O + Cl2
H2O2 + S + NaOH = Na2SO4 + H2O =>
3 H2O2 + S + 2 NaOH = Na2SO4 + 4 H2O
NaCl(aq) + Hg2(C2H3O2)2(aq) = NaC2H3O2 + HgCl =>
2 NaCl(aq) + Hg2(C2H3O2)2(aq) = 2 NaC2H3O2 + 2 HgCl
U3O8 + HNO3 = UO2(NO3)2 + NO2 + H2O =>
U3O8 + 8 HNO3 = 3 UO2(NO3)2 + 2 NO2 + 4 H2O
C6H14O2 + KI + H2SO4 = C6H14I2 + H2O + K + HSO4 =>
C6H14O2 + 2 KI + 4 H2SO4 = C6H14I2 + 2 H2O + 2 K + 4 HSO4
CHI + NaOH = NaCI + H2O =>
CHI + NaOH = NaCI + H2O
C4H10 + F2 = C4H8F2 + H2 =>
C4H10 + F2 = C4H8F2 + H2
CuCl2 + Na2CO3 + H2O = Cu(OH)2 + NaCl + CO2 =>
CuCl2 + Na2CO3 + H2O = Cu(OH)2 + 2 NaCl + CO2
SbH3 + KClO3 + KOH + H2O = K[Sb(OH)6] + KCl =>
3 SbH3 + 4 KClO3 + 3 KOH + 3 H2O = 3 K[Sb(OH)6] + 4 KCl
Na2SiO3 + H2O = Na2Si2O5 + NaOH =>
2 Na2SiO3 + H2O = Na2Si2O5 + 2 NaOH
H2SO4 + Ba(CH3CO4)2 = H2O + CO + BaSO4 =>
H2SO4 + Ba(CH3CO4)2 = 4 H2O + 4 CO + BaSO4
KNO2 + (NH4)2SO4 = K2SO4 + NH4NO2 =>
2 KNO2 + (NH4)2SO4 = K2SO4 + 2 NH4NO2
Zn(OH)2 + NaOH = Na2(ZnO2) + H2O =>
Zn(OH)2 + 2 NaOH = Na2(ZnO2) + 2 H2O
CaCl2 + (NH4)4[Fe(CN)6] = Ca2[Fe(CN)6] + NH4Cl =>
2 CaCl2 + (NH4)4[Fe(CN)6] = Ca2[Fe(CN)6] + 4 NH4Cl
Al2O3(s) + HCl(ac) = AlCl3 + H2O =>
Al2O3(s) + 6 HCl(ac) = 2 AlCl3 + 3 H2O
NiCl2 + F2 = FCl3 + Ni =>
3 NiCl2 + F2 = 2 FCl3 + 3 Ni
C2H5OH + KMnO4 + H2SO4 = C2H4O2 + MnSO4 + K2SO4 + H2O =>
5 C2H5OH + 4 KMnO4 + 6 H2SO4 = 5 C2H4O2 + 4 MnSO4 + 2 K2SO4 + 11 H2O
Fe(OH)3 + H3PO4 = FePO4 + H2O =>
Fe(OH)3 + H3PO4 = FePO4 + 3 H2O
(K4Fe(CN)6)24 + (KMnO4)24 + H2SO4 = KHSO4 + Fe2(SO4)3 + (MnSO4)24 + (HNO3)24 + (CO2)24 + H2O =>
5(K4Fe(CN)6)24 + 61(KMnO4)24 + 3588 H2SO4 = 1944 KHSO4 + 60 Fe2(SO4)3 + 61(MnSO4)24 + 30(HNO3)24 + 30(CO2)24 + 2256 H2O
Nb2W2C3F2 = WC + Nb6C5 + WF6 + W =>
3 Nb2W2C3F2 = 4 WC + Nb6C5 + WF6 + W
Sr(OH)2 + Al(NO3)3 = Sr(NO3)2 + Al(OH)3 =>
3 Sr(OH)2 + 2 Al(NO3)3 = 3 Sr(NO3)2 + 2 Al(OH)3
AgNO3 + Zn(ii) = Zn(NO3)2 + Ag =>
2 AgNO3 + Zn(ii) = Zn(NO3)2 + 2 Ag
H2SeO3 + H2S = Se + H2S04 + H2O =>
3 H2SeO3 + 8 H2S = 3 Se + 2 H2S04 + 9 H2O
I{-} + MnO4{-} + H3O{+} = I2 + Mn{2+} + H2O =>
10 I{-} + 2 MnO4{-} + 16 H3O{+} = 5 I2 + 2 Mn{2+} + 24 H2O
H2(g) + Cu(NO3)2(aq) = Cu(s) + HNO3(aq) =>
H2(g) + Cu(NO3)2(aq) = Cu(s) + 2 HNO3(aq)
H2SO3 + O2 = H2SO4 =>
2 H2SO3 + O2 = 2 H2SO4
CaCl2 + ZnCO3 = ZnCl2 + CaCO3 =>
CaCl2 + ZnCO3 = ZnCl2 + CaCO3
Cu + Hg(NO3)2 = Cu{-} + Hg(NO3)2{+} =>
Cu + Hg(NO3)2 = Cu{-} + Hg(NO3)2{+}
Zn(OH)3 = H2O + O2 + Zn =>
4 Zn(OH)3 = 6 H2O + 3 O2 + 4 Zn
NH4NO3 + NaOH = NaNO3NH3H2O =>
NH4NO3 + NaOH = NaNO3NH3H2O
KNO3 + Na3Co(NO2)6 = K3Co(NO2)6 + NaNO3 =>
3 KNO3 + Na3Co(NO2)6 = K3Co(NO2)6 + 3 NaNO3
Mn + MgO = Mg + MnO =>
Mn + MgO = Mg + MnO
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 |
Equations balanced on the previous day | Equations balanced on the next day |
Equations balanced on 01/16/25
Equations balanced on 02/15/24
Please let us know how we can improve this web app.